Use Cutting Enzymes to Encode the Secret Message - Saadoun A. (Al-Rafidain Journal of Computer Sciences and Mathematics)
Researchers begin to explore new methods to manage the huge amount of data shared over the Internet, in order to use them more efficiently and safely, One of the ways that is raised nowadays is Steganography, The art of information hiding within electronic media. Steganography ways vary in their approaches for hiding information. During this research designed algorithm that using restriction enzymes to cutting sequence of DNA, the fragments  resulted was used to building symbols table (character , number , special character,…),by using symbols table the plain message (text ,sound ,image ,video) coding to DNA and sent it to recipient, the recipient build symbols table same way in the sender site and use function to known restriction enzymes, using restriction enzymes to cutting  secret sequence DNA , by using the fragments of DNA and symbols table can  retrieve the plain message  (text ,sound ,image ,video).